(untitled) (Palíndromo, 2017)
The present text discusses curatorial practices from the perspective of a production in art. It addresses issues such as the objective versus subjective relation that the curator and the artist maintain with the works of art, the particularities that involve the artist-curator practice, as well as the relationship between the organizational/bureaucratic instances and the exercise of curatorship. Authors and artists such as Ricardo Basbaum, Arthur Bispo do Rosário, Maria Esther Maciel, Jacques Rancière, and Cristiana Tejo, with their artistic, reflective and/or curatorial practices, help to understand the curator’s offices, at the same time as they provoke thought in the attempt to weave other perspectives under the action of this emblematic as well as essential professional in the field of contemporary art.